Economic voting in provincial elections: Revisiting electoral accountability in the Canadian provinces. Issue 3 (27th May 2019) - González-Sirois, Gaby; Bélanger, Éric
ABSTRACT: We examine the outcomes of the provincial elections having been held in Canada since the Great Recession and compare them with outcomes from past decades. Given the severity of the 2008 financial crisis, we test for whether provincial governments' electoral fortunes over the recent period have been negatively impacted by this important economic shock. Our analyses of aggregate-level provincial electoral outcomes: (1) confirm that provincial incumbent parties are held accountable for provincial economic conditions; (2) show that this provincial economic voting pattern has been heightened during the financial crisis; and (3) demonstrate that provincial incumbents also incur vote share losses when national economic conditions worsen and their respective family party is in power at the federal level, although this referendum voting pattern appears to have been unaffected by the financial crisis.